The Application Effect of Learning Model Acquisition Concept Combined with Cooperative Learning STAD to the Learning Achievement, activeness, and Students Responses In Learning Chemistry Bond - Putri Ridha Ilahi (Jurnal Pendidikan Sains, 2013)
Pengaruh Penerapan Model Pembelajaran Pemerolehan Konsep Dipadu Pembelajaran Kooperatif STAD terhadap Prestasi Belajar, Keaktifan, dan Respon Siswa pada Pembelajaran Ikatan Kimia Abstract: This study aims to determine differences: (1) student achievement acquisition make use of the concept of combined learning model STAD cooperative learning and student achievement using model concepts in conventional learning acquisition; (2) active students use learning model acquisition combined the concept of cooperative learning and student activity STAD learning model acquisition using the concept in the conventional learning; (3) The students 'response to the acquisition of the concept of combined learning STAD cooperative learning and students' response to the acquisition of learning concepts in conventional learning. This research uses descriptive research design and quasi-experimental design (quasy experiment design). Learning achievement data were collected using an objective test and reliability coefficient calculated by using SPSS 16 for windows Data recorded in the learning activity of students using observation sheet. Student response data to the learning model was obtained by questionnaire. Data were analyzed statistically and descriptive. The results showed: (1) student achievement using learning model acquisition combined the concept of cooperative learning STAD higher compared to student achievement using model concepts in conventional learning acquisition; (2) active students use learning model acquisition combined the concept of cooperative learning STAD higher than students' active learning model acquisition using the concept in the conventional learning; (3) The students 'response to learning acquisition combined the concept of cooperative learning STAD is more positive than the students' response to the acquisition of learning concepts in conventional learning. Key Words: acquisition of concepts, STAD, chemical bonds   Abstrak: Penelitian ini bertujuan untuk mengetahui perbedaan: (1) prestasi belajar siswa menggunakan model pembelajaran pemerolehan konsep dipadu pembelajaran kooperatif STAD dan prestasi belajar siswa menggunakan model pembelajaran pemerolehan konsep dalam pembelajaran konvensional; (2) keaktifan siswa menggunakan model pembelajaran pemerolehan konsep dipadu pembelajaran ko-operatif STAD dan keaktifan siswa menggunakan model pembelajaran pemerolehan konsep dalam pembelajaran konvensional; (3) respon siswa terhadap pembelajaran pemerolehan konsep dipadu pembelajaran kooperatif STAD dan respon siswa terhadap pembelajaran pemerolehan konsep dalam pembelajaran konvensional. Penelitian ini menggunakan rancangan penelitian deskriptif dan rancang-an eksperimen semu (quasy experiment design). Data prestasi belajar dikumpulkan menggunakan tes objektif dan koefisien reliabilitas dihitung dengan menggunakan SPSS 16 for windows. Data ke-aktifan siswa dalam pembelajaran direkam menggunakan lembar observasi. Data respon siswa terhadap model pembelajaran diperoleh dengan angket. Data dianalisis secara statistik dan deskriptif. Hasil penelitian menunjukkan: (1) prestasi belajar siswa menggunakan model pembelajaran pemerolehan konsep dipadu pembelajaran kooperatif STAD lebih tinggi dibandingkan dengan prestasi belajar sis-wa menggunakan model pembelajaran pemerolehan konsep dalam pembelajaran konvensional; (2) keaktifan siswa menggunakan model pembelajaran pemerolehan konsep dipadu pembelajaran koopera-tif STAD lebih tinggi dibandingkan keaktifan siswa menggunakan model pembelajaran pemerolehan konsep dalam pembelajaran konvensional; (3) respon siswa terhadap pembelajaran pemerolehan konsep dipadu pembelajaran kooperatif STAD adalah lebih positif dibandingkan dengan respon sis-wa terhadap pembelajaran pemerolehan konsep dalam pembelajaran konvensional.Kata kunci: pemerolehan konsep, STAD, ikatan kimia